Ecolinguistics at the Core of Scientific Language Construction and Nationally Oriented Language Policy - Adilkhanyan, Anahit; Aghajanyan, Zarik (Bulletin of Yerevan University B: Philology, 2025)
The article addresses issues related to a new branch of linguistics—ecolinguistics. Language, as a national existential system and a formula of national thought, is determined not only by the linguistic cognition and worldview of the individual speaker but also by the interrelationship and interaction between language, humans, and the environment. In this multifaceted chain, the surrounding environment directly influences human speech activity. Naturally, if the preservation of the natural ecosystem is being discussed, attention should also be paid to the purity and preservation of one of its integral components—language, as an innate human capacity.The ecology of language is akin to environmental ecology, with both operating under the guiding principles of maintaining and restoring harmony. In the 21st century, it is crucial to emphasize a new type of linguistic cognition—ecological linguistic thinking—which involves viewing language as an irreplaceable component in the interplay between humans, society, and nature. In this context, the ecology of language serves as a tool for protecting language from social and negative influences.  Ecolinguistics  investigates the sources of language pollution and seeks solutions to these complex issues. It aims to provide an objective picture of language development, warn linguistic communities of threats and pollution endangering the language, and thereby foster care and attention toward the fate of literary language and the speech environment of humans and society.
Keywords: Ecolinguistics; ecological linguistic thinking; humans; society; nature; individual speaker; language and speech ecology; driving force; harmony; environment